Severe colic in a newborn dairy calf caused by a large colostrum curd: a case report - Sockett, Donald C.; Pohly, Andrea E.; Deering, Kathleen M.; Breuer, Ryan M. (Frontiers in Veterinary Science, 2024)
A newborn female, Holstein calf weighing approximately 38.5 kg developed severe, persistent colic caused by a large colostrum curd located within the calf's abomasum. Based upon 10% body weight, the calf had been fed 4 liters (L) of firstmilking colostrum approximately 30-minutes after birth and an additional 2L of firstmilking colostrum six hours after the first feeding. Both the first and second feedings used an esophageal tube feeder to deliver the colostrum. Colic developed shortly after the second colostrum feeding. The affected calf did not respond to on-farm supportive medical therapy and was humanely euthanized by a penetrating captive bolt roughly 22 hours after the onset of colic. This on-farm colostrum feeding protocol is routinely observed in the current dairy industry. This case demonstrates calves that are fed large volumes of colostrum during a relatively short window of time may develop a large, firm colostrum curd within the abomasum that causes abdominal distension, colic, and occasional death. There is an urgent need for prospective analytical studies that determine the optimal immunoglobulin mass (g/L), and ideal volume of colostrum fed to newborn calves for both the first and second colostrum feedings within the most beneficial time frame. Guidelines should be developed that minimize complications which adversely affect calf health and wellbeing while ensuring successful transfer of passive immunity.